Unveiling Soil Fertility Dynamics in Rawalpindi Region: Implications for Sustainable Agriculture and Fertilizer Strategies - Alvi, Sarosh; Qazi, Muhammad Akram; Rashid, Muhammad; Afzal, Sher; Raza, Raja Abad; Shah, Muhammad Tahir; Khan, Saftain Ullah; Ali, Sajid; Iqbal, Hafiz Imran (Journal of Agriculture and Veterinary Science, 2024)
In Pakistan, the adoption of high-yielding crop varieties and intensive farming practices since the commencement of the green revolution has led to a degradation in soil quality and fertility. Particularly in rainfed areas, rapid mineralization of soil organic matter (SOM) has exacerbated widespread nutrient deficiencies. This study, conducted in Rawalpindi district, aimed to evaluate the extent of soil nutrient deficiencies to formulate precise fertilizer recommendations for management of soil health and fertility to obtain sustainable crop production. A comprehensive analysis of 4080 soil samples from various tehsils within Rawalpindi district was carried out. Results revealed that the majority of soils (79%) were classified as loam, with an overwhelming percentage (88%) exhibiting alkaline pH (7.5 to 8.5). Furthermore, 99% of soils had an electrical conductivity (EC) within the safe limit of
Keywords: Cultivated land; Fertility status; Soil nutrients; Spatial distribution; Rawalpindi